Meningkatkan Kualitas Pelayanan Publik Kantin UNESA Ketintang melalui Pengembangan Komunikasi Intrapersonal - Rahmadani, Salsabila Riska; Nita, Sutri Rachma; Prasetijowati, Tri (IAI Nasional Laa Roiba Bogor, 2026)
The growth of the food and beverage industry in the UNESA canteen, which is so rapid, has led to increasingly intense competition. Service quality can influence consumers' purchasing decisions regarding a product, especially in the service sector. Good service quality in the UNESA Ketintang canteen is intended as a stimulus for purchasing decisions at the Surabaya State University canteen. This study attempts to explain the effect of service quality on consumers' purchasing decisions at the Surabaya State University canteen, both partially and simultaneously. The population in this study is infinite. The sampling technique was done using accidental sampling, where samples are taken by chance and not predetermined or planned in advance. The sample used in this study consisted of 3 respondents. The data analysis tools used in this study are multiple linear regression analysis and questionnaires as tools for collecting respondent data. Based on the adjusted R2 value of 0.343, it means that service quality affects consumer purchasing decisions at the Surabaya State University canteen by 34.3%, while the remaining 65.7% is influenced by other variables outside of this study. The results of the study indicate that there is a simultaneous effect of service quality on purchasing decisions at the Surabaya State University canteen. Furthermore, the study results show that the responsiveness variable is the most influential variable on purchasing decisions at the Surabaya State University canteen.